(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
This article uses the CN Tower and Calgary Tower to explore how the architectural form of the tower possesses a number of characteristics we typically associate with media technologies. To appreciate what we call “tower-mediality,” we start first with a brief discussion of the scholarly literature on towers, highlighting that while much is said about towers’ symbolic value, little attention has been devoted to thinking of these forms in material and infrastructural terms. Then we turn to the Canadian towers themselves, asking, first, why they have received so little scholarly attention, before suggesting some points of intersection between architecture and communication research. Finally, we offer three registers—ritual, perspective, and spectacle—by which to explore the mediality of the CN and Calgary Towers. In undertaking this analysis, we attempt to expand the vocabulary available for understanding how towers are platforms that mediate the temporal and spatial elements of civic culture and to invite further considerations of the mediating and communicative work that occurs along the vertical axis.